Overcoming resistance to innovations: an approach for the use of communication tools within the innovation process. (29th June 2009) - Dorner, Nadin; Gurtner, Sebastian; Schefczyk, Michael
The objective of this article is to show the need for a situation-adapted use of specific communication tools within the different phases of the innovation process. Therefore, this research provides an approach on how activities, objectives and resistance change during the innovation process. Eventually, it is shown how a key person can use specific communication tools to foster innovation and overcome internal resistance.